A new creep law for crushable aggregates - McDowell, Glenn R.; de Bono, John P. (ICE Publishing, 2013)
The authors have recently proposed a new equation for the one-dimensional (1D) normal compression line, which contains a parameter controlling the size effect on average strength. They showed that the equation held for a wide range of discrete-element modelling (DEM) simulations of crushable aggregates. This paper incorporates the time-dependence of particle strength. A new equation is proposed and examined using DEM of 1D creep. The simulations show that while the plots may seem linear on a plot of voids ratio against the logarithm of time in the traditional way, the new proposed law, which is linear when the voids ratio is also plotted on a logarithmic scale, is more appropriate. The simulations examine the influence of the size effect hardening law, the time dependence on strength and stress level. It is shown that the new equation holds for each case.